High field pulsed terahertz measurements of nonlinear conductivity - A. G. Markelz (Nonlinear Optics: Materials, Fundamentals, and Applications, 2000)
High field pulsed terahertz spectroscopy is used to measure the inplane nonlinear conductivity response of two dimensional electron gases. Results are compared to FEL measurements suggesting LO phonon bottleneck weakening at 0.5 THz.
Keywords: 0.5 THz; 2D electron gases; Conductivity measurement; electrical conductivity measurement; Electron emission; FEL measurements; Finite impulse response filter; high field pulsed terahertz measurements; high field pulsed terahertz spectroscopy; high-speed optical techniques; inplane nonlinear conductivity response; LO phonon bottleneck weakening; nonlinear conductivity; nonlinear optics; phonons; Power measurement; Pulse measurements; Resonance; semiconductor quantum wells; spectroscopy; Submillimeter wave measurements; submillimetre wave spectroscopy; two dimensional electron gases; two-dimensional electron gas